Effectiveness of a blood culture bundle in reducing contamination rates in a neonatal intensive care unit - Şebnem Çalkavur; Oğuz Han Kalkanlı; Tuna Ketenci; Nazan Kavas; Miray Yılmaz Çelebi; Arzu Bayram; İlker Devrim (The Turkish Journal of Pediatrics)
Background. Isolating microorganisms from blood cultures is the gold standard for identifying the cause of sepsis. However, contamination of the blood culture is a significant barrier to the blood culture’s utility. In this study, we aimed to evaluate the impact of blood culture bundles on the incidence of contamination in the neonatal intensive care unit (NICU).